Development of Interactive Media Articulate Storyline 3 based on Problem based Learning in Class V Elementary School - Waldi, Atri; Reinita, Reinita; Desyandri, Desyandri; Viola, Firdha Okta (Program Studi Pendidikan Guru Sekolah Dasar, FKIP, Universitas Riau, 2024)
The background of this study is not enough availability of various learning media in the learning process so that impact to interest participant educate for active in learning. The objective of the study is to develop interactive media Articulate Storyline 3 based Problem Based Learning in class V SD that is valid, practical and effective . The research method used is R&D research with the ADDIE development model. Developed product load material thematic integrated theme 6 in class V SD with results study show the average value of interactive media validity is 92.6% very valid category, the results of interactive media practicality test show mark practicality for teacher and participant responses educate are 93.7% and 94.5%. Test the effectiveness of interactive media seen from the learning outcomes of students after using interactive media Articulate Storyline 3, namely obtaining 82% and 91% completeness with a student score of 70 or more. From these results, it shows that the interactive media Articulate Storyline 3 based on Problem Based Learning that has been developed is declared feasible, practical and effective for use in teaching and learning activities.